Penerapan Prinsip New Public Service dalam Pelayanan PUSPAGA untuk Pencegahan Kekerasan terhadap Anak di Kota Tanjungpinang Tahun 2025 - Wan Maulidia; Nur Aslamaturrahmah Dwi Putri; Novi Winarti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Violence against children remains an issue requiring prevention efforts through public services oriented toward the best interests of the child and the strengthening of family resilience. As a preventive service managed by the Office of Women's Empowerment, Child Protection, and Community Empowerment (DP3APM), the Family Learning Center (PUSPAGA) of Tanjungpinang City plays a role in providing education, consultation, and support to families. However, the implementation of PUSPAGA services faces challenges such as uneven outreach, suboptimal cross-sector coordination, and limited staff capacity. This study aims to analyze the application of the seven principles of New Public Service (NPS) within PUSPAGA Tanjungpinang City's services in 2025. A descriptive qualitative approach was employed. Data were collected through interviews and documentation involving six informants, comprising representatives from DP3APM, PUSPAGA staff, parents receiving services, and school teachers. Data analysis utilized the Miles, Huberman, and Saldana model. The results indicate that PUSPAGA services have implemented the seven NPS principles: serving citizens, prioritizing the public interest, valuing citizenship, thinking strategically and acting democratically, understanding the complexity of accountability, serving rather than steering, and valuing people. The application of these principles is reflected in services such as consultation, counseling, parenting education, support, referrals, confidentiality protection, and cross-sector collaboration. Nevertheless, implementation remains suboptimal; therefore, strengthening outreach, coordination, and staff capacity is necessary to ensure PUSPAGA services become increasingly responsive, inclusive, and oriented toward fulfilling children's rights and fostering family resilience.